Work Hours: A Resident’s Reflection on Time - Orr, Andrew R (Ars Medica, 2020)
This short essay explores the concept of time in medicine through the construct of kairos, the transcendent character of a given moment. Reflecting on a powerful experience during training, a former medical resident examines the heart of the doctor-patient relationship using this lens and wonders about current barriers to its practical application. By suggesting several paradigm shifts for the health system at large and advocating for a return to social connection guided by the medical humanities, the author hopes to encourage readers to help create space together to recognize the power of everyday moments in patient care.